Resposta hemodinâmica fetal ao exercício isométrico materno - Soares, Karina Biaggio (2018)
Objectives: To assess the fetal response by use of doppler study in low risck pregnant women submitted to isometric handgrip test. Methods: A cross-sectional experimental study was conducted on 50 healty pregnant women with gestational age between 26 and 36 weeks. The patients were submited to isometric handgrip, and data were collected from the mother (blood pressure, heart rate and Doppler velocimetry for the uterine arteries) and from the fetus (heart rate, Doppler velocimetry for the umbilical artery, middle cerebral artery and ductus venosus). All variables were collected before, during and after the isometric handgrip. Results: There was a significant increase (p<0,001) of systolic blood pressure (pre-isometric 113,13±9,92, trans-isometric 117,13±10,24, post-isometric 112,43±9,87) and maternal heart rate (pre 87,52±14,10, trans 97,61±14,83, post 85,13±13,24), and a significant decrease of pulsatility index (pre 0,63±0,15, trans 0,56±0,15, post 0,65±0,17, p=0,001), resistance index (pre 0,44±0,08, trans 0,40±0,07, post 0,45±0,08, p=0,001) and systole/diastole ratio (pre 1,81±0,26, trans 1,69±0,24, post 1,85±0,29, p<0,001) of the left uterine artery. These maternal variables changed significantly only during isometry, but not when pre and post data were compared. There was no change on the fetal parameters when compared before, during or after isometric handgrip. Although there was no significant reduction of pulsatility index, resistance index and systole/diastole ratio values for the right uterine artery during the isometric handgrip, it had the same behavior of the left uterine artery, showing that there was a bilateral vasodilatation when maternal blood pressure and heart rate rise. This vasodilatation of the uterine arteries seems to be a compensatory mecanism, preserving the hemodynamic homeostasis of pregnancy, which is confirmed by the fact of there was no change on the fetal hemodynamic parameters. Conclusion: The isometric handgrip test didn’t interfered in the fetal hemodynamics, in low risk pregnant women.